A new species of Phlogiellus Pocock, 1897 from China (Araneae: Theraphosidae) - Wang, Zhongjing; Yao, Yanbin; Huang, Shihui; Gong, Jiaxian; Yu, Haiyue; Liu, Keke (Zootaxa, 2026)
A new species of theraphosid spider, Phlogiellus hakka Yao, Gong, Yu & Liu, sp. nov., is described from Fujian Province, southern China, based on both male and female specimens. This represents the first record of the genus Phlogiellus Pocock, 1897 from Fujian Province. Detailed morphological descriptions, supported by digital images (including SEM), and information on its natural habitat are provided. The discovery of P. hakka sp. nov. fills a significant distributional gap along the southeastern coast of China and is discussed in relation to the known biogeography of the genus in the region.